Overview of Carpal Tunnel Syndrome Events at Tarakan Hospital in 2019-2021 - Evan Evan; Monica Cherlady Anastasia; Sefaca Sulistiyanto Jusuf (Jurnal MedScientiae, 2023)
Excessive activity on the hands or wrists will be very risky for experiencing one of the diseases, namely carpal tunnel syndrome. According to the American Academy of Family Physicians, the incidence of carpal tunnel syndrome is 329 cases per thousand people per year. Another study says the incidence of carpal tunnel syndrome in the United States is about 150 cases per thousand people per year. While the incidence of carpal tunnel syndrome in Indonesia itself is not known with certainty. This study aims to determine the distribution of age, gender, and occupation on the incidence of carpal tunnel syndrome at the Tarakan Regional General Hospital in 2019-2021. The research method is a descriptive method with a cross sectional approach, data is taken from the medical records of Tarakan Hospital in 2019-2021 with a diagnosis of carpal tunnel syndrome which is enforced based on NCS - EMG examinations until the minimum number of samples is met. The results showed that age (46-55 years), women, and occupations of administrative staff ranked first and it could be concluded that they had a higher risk of developing carpal tunnel syndrome.